1988
DOI: 10.1002/chin.198823361
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Proton Conduction in Sintered Oxides Based on BaCeO3.

Abstract: ChemInform Abstract Some sintered BaCeO3-based ceramics are found to exhibit appreciable protonic conductivity in water or hydrogen containing atmospheres, although they are p-type conductors in dry atmospheres. The protonic conductivities of Nd2O3-, La2O3-, or Y2O3-doped BaCeO3 ceramics are higher than that of Yb2O3-doped SrCeO3. The BaCeO3-based materials may be applicable as solid electrolytes in hydrogen fuel cells, hydrogen pumps, and steam electrolyzers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(87 citation statements)
references
References 1 publication
3
84
0
Order By: Relevance
“…Fuel cell test of BYZ thin film using platinum ink for both electrodes have been performed. Successful fuel cell measurements were carried out with a peak power density of 28 mW/cm 2 . It was shown the anode rather than the cathode is the most resistive electrode.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fuel cell test of BYZ thin film using platinum ink for both electrodes have been performed. Successful fuel cell measurements were carried out with a peak power density of 28 mW/cm 2 . It was shown the anode rather than the cathode is the most resistive electrode.…”
Section: Discussionmentioning
confidence: 99%
“…A maximum 25mW/cm 2 was achieved at 600C, Figure Impedance measurements of symmetric cell in oxygen show a total resistance of 6.9 ohm*cm 2 of which 4 ohm*cm 2 is due to the electrolyte, Figure 26. This implies a cathode resistance of 1.45 ohm*cm 2 . Similarly an anode resistance of 5.5 ohm*cm 2 is calculated.…”
Section: Baseline Fuel Cell Performance Demonstrationmentioning
confidence: 99%
See 1 more Smart Citation
“…The proton transfer occurs from higher vapour pressure side, which is the negative pole on lower vapour pressure side. The reactions at each electrode are given as under [56]:…”
Section: Solid-electrolyte Typementioning
confidence: 99%
“…Since Iwahara et al [1,2] first reported the proton conduction phenomenon in the ABO3 perovskite compounds of doped strontium cerates and doped barium cerates, many doped perovskite-type cerates and zirconates compounds have been investigated intensively, especially during the recent years [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. However, high sintering temperatures (normally higher than 1600 ℃) and long sintering times (more than 24 h) are always needed for BaCeO3-and BaZrO3-based ceramic materials to obtain dense bulk materials.…”
Section: Introductionmentioning
confidence: 99%